Abnormal brain activity in lumbar disc herniation patients with chronic pain is associated with their clinical symptoms - Tang, Cheng; Guo, Guangxin; Fang, Sitong; Yao, Chongjie; Zhu, Bowen; Kong, Lingjun; Pan, Xuanjin; Li, Xinrong; He, Weibin; Wu, Zhiwei; Fang, Min (Frontiers in Neuroscience, 2023)
Lumbar disc herniation, a chronic degenerative disease, is one of the major contributors to chronic low back pain and disability. Although many studies have been conducted in the past on brain function in chronic low back pain (cLBP), most of these studies did not classify chronic low back pain patients according to their etiology. The lack of etiologic classification may lead to inconsistencies between findings, and the correlation between differences in brain activation and clinical symptoms in lumbar disc herniation patients with chronic low back pain (LDHCP) was less studied in the past. In this study, 36 LDHCP patients and 36 healthy controls (HCs) were included to study brain activity abnormalities in LDHCP. Visual analogue scale (VAS), oswestry disability index (ODI), self-rating anxiety scale (SAS), self-rating depression scale (SDS) were used to assess clinical symptoms. The results showed that LDHCP patients exhibited abnormally increased and diminished activation of brain regions compared to HCs. Correlation analysis showed that the amplitude of low frequency fluctuations (ALFF) in the left middle frontal gyrus is negatively correlated with SAS and VAS, while the right superior temporal gyrus is positively correlated with SAS and VAS, the dorsolateral left superior frontal gyrus and the right middle frontal gyrus are negatively correlated with VAS and SAS, respectively. These brain areas may be related to the severity of pain and negative emotions in LDHCP patients.